Investigation on the Therapeutic Effect of Polygonum multiflorum Thunb. in Chronic Stress-Induced Hair Loss in Mice Coupled with Metabolomics and Proteomics - Yong-Kang Zhao; Rui-Xian Guo; Rui-Sheng Li; Wei Shi; Hai-Ying Gong; Run-Ran Ma; Han Gao; Zhen Li; Ke-Jian Hu; Zhao-Fang Bai; Xiao-He Xiao; Qing-Ce Zang; et al. (World Journal of Traditional Chinese Medicine)
Objective: Stress is the main factor that leads to hair loss, and no effective therapeutics have been developed for stress alopecia. Polygonum multiflorum Thunb. (PM) is a famous traditional Chinese medicine for tonifying the kidney and nourishing the liver, which is used to treat hair loss. This study aimed to demonstrate that PM is a promising agent for the treatment of chronic stress-induced hair loss. Materials and Methods: C57BL/6J male mice were subjected to chronic restraint stress to inhibit hair follicle growth. Subsequently, the effect of PM was examined by oral administration of the PM water extract or cortisone, followed by histological analysis, immunofluorescence of follicle samples, serum metabolomics, and adrenal proteomics. Results: Hair regeneration in a mouse model was severely inhibited by chronic restraint stress. After PM treatment, hair regeneration in model mice was promoted, including an increased length of hair shafts in skin sections, an increased number of 5-Ethynyl-2’-deoxyuridine-positive cells, and a decreased number of apoptotic cells around the hair follicles. The various test indicators of these PM-treated mice almost recovered to levels comparable to those of the control mice. Through metabolomics and proteomics analyses, we identified 181 endogenous differential metabolites and 75 differential proteins, which may be the potential targets for PM. Pathway enrichment analysis showed that steroid biosynthesis (the main pathway through which stress leads to an imbalance in glucocorticoid secretion by the adrenal gland) may play an important role in the therapeutic effects of PM. In addition, omics analysis revealed that glycolysis/gluconeogenesis, pyruvate metabolism, lipid metabolism, and other glucocorticoid-related metabolic pathways differed significantly after PM treatment. Conclusions: PM is an important natural drug that regulates hair regeneration in mice under stress, and its underlying mechanism is closely related to the regulation of adrenal glucocorticoids and their metabolism.